Hubungan Postur Kerja Pengguna Komputer Dengan Keluhan Muskuloskeletal Pada Staf Logistik Jakarta Timur - Chairunisa, Ratu; Susilowati, Indri Hapsari; Pujiriani, Ike (Jurnal Kesehatan Holistic, 2024)
Background: Working using computer or also known as video display terminal (VDT) is a work which have a high risk of musculoskeletal disorder. The posture of body during work is one of the factors which may have effect on musculoskeletal disorder. Objective: The research was to discover the correlation of the working posture of computer user two towards musculoskeletal disorder on the Staffs of X Logistics East Jakarta. Methods: The research used cross sectional while the sampling was conducted using purposive sampling technique. The amount of sample for quantitative research is 79 respondents, while the amount of sample for qualitative research is 8 respondents. Respondents were analyzed using Rapid Office Strain Assessment (ROSA), Nordic Body Map (NBM), Global Physical Activity Questionnaire (GPAQ) version 2 and Copenhagen Psychosocial Questionnaire III (CopSoq III). Results: The result of research showed that, from 79 respondents, there were (45.6%) low category musculoskeletal disorder and (54.4%) moderate category musculoskeletal disorder. Statistical test analysis with Chi Square test (CI=95% and = 5%) showed the results of correlation between individual factors and musculoskeletal disorder, namely age (p=0.002), gender (p=0.000), physical activity (p=0.017) , duration of work (p=0.000), and unrelated factors, namely smoking habits (p=0.288), and work posture (p=0.641), chairs (p=1), desks (p=0.464), psychosocial (p=0.286), work demands (p=0.805), organizational characteristics and work content (p=1), interpersonal relationships at work and leadership (p=0.540). Conclusion: Based on the analysis, the factors which influenced musculoskeletal disorder on Staffs of X Logistics in East Jakarta are age, gender, physical activity, and duration of work.